Obesity and reduction of the response rate to anti–tumor necrosis factor α in rheumatoid arthritis: An approach to a personalized medicine - Gremese, Elisa; Carletto, Antonio; Padovan, Melissa; Atzeni, Fabiola; Raffeiner, Bernd; Giardina, Anna Rita; Favalli, Ennio Giulio; Erre, Gian Luca; Gorla, Roberto; Galeazzi, Mauro; Foti, Rosario; Cantini, Fabrizio; et al. (Arthritis care & research (2010), 2013)
Objective Obesity is a mild, long‐lasting inflammatory disease and, as such, could increase the inflammatory burden of rheumatoid arthritis (RA). The study aim was to determine whether obesity represents a risk factor for a poor remission rate in RA patients requiring anti–tumor necrosis factor α (anti‐TNFα) therapy for progressive and active disease despite treatment with methotrexate or other disease‐modifying antirheumatic drugs. Methods Patients were identified from 15 outpatient clinics of university hospitals and hospitals in Italy taking part in the Gruppo Italiano di Studio sulle Early Arthritis network. Disease Activity Score in 28 joints (DAS28), body mass index (BMI; categorized as <25, 25–30, and >30 kg/m2), acute‐phase reactants, IgM rheumatoid factor, and anti–cyclic citrullinated peptide antibody values were collected. DAS28 remission was defined as a score of <2.6 lasting for at least 3 months. Results Six hundred forty‐one outpatients with longstanding RA receiving anti‐TNFα blockers (adalimumab, n = 260; etanercept, n = 227; infliximab, n = 154), recruited from 2006–2009 and monitored for at least 12 months, were analyzed. The mean ± SD DAS28 at baseline was 5.6 ± 1.4. A BMI of >30 kg/m2 was recorded in 66 (10.3%) of 641 RA patients. After 12 months of anti‐TNFα treatment, a DAS28 of <2.6 was noted in 15.2% of the obese subjects, in 30.4% of the patients with a BMI of 25–30 kg/m2, and in 32.9% of the patients with a BMI of <25 kg/m2 (P = 0.01). The lowest percentage of remission, which was statistically significant versus adalimumab and etanercept (P = 0.003), was observed with infliximab. Conclusion Obesity represents a risk factor for a poor remission rate in patients with longstanding RA treated with anti‐TNFα agents. A personalized treatment plan might be a possible solution.